Geochemical and geochronological evidence of the Pataz Batholith between parallels 8°10'S - 8°17'S - López Mogrovejo, Willy (2022)
The Carboniferous (Mississippian) Pataz Batholith, dated between 329 - 347 Ma (Haeberlin et al., 2004) is about 160 km long (N30°W), 2.5 to 5 km wide currently recognized.  The intrusive is constituted by more than one plutonic facies: one facies of granite - granodiorite and another facies of tonalite-diorite, being the first one the most favorable for the emplacement and development of orogenic veins with gold content. The study area is located between parallels 8°10'S to 8°17'S, nearby the towns of Llacuabamba and Tayabamba in the province of Pataz, Peru, studies carried out on the intrusives outcropping in the vicinity of the town of Tayabamba would have shown a petrological and geochemical affinity to the Pataz Batholith, the affinity of all samples towards volcanic arc granites, as a SiO2 vs Sm/Yb ratio affinity presumes a possible coetaneity of the crystalline pulses (Mantle & Collins, 2008) has been corroborated with the U-Pb geochronological results obtained, which place the intrusives of the study area between 333 - 335 Ma, affirming the continuity of the Pataz Batholith to the south.